2010
DOI: 10.1111/j.1600-0528.2010.00552.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dental anxiety and irregular attendance on referral for dental treatment under sedation within the National Health Service in London

Abstract: Objective-To investigate whether the relationship between dental anxiety and referral for treatment under sedation is explained by attendance patterns and oral health. Methods-Structural EquationModeling was used on the covariance matrix of the covariates to test hypothesized inter-relationships. Subsequently, we modeled the probability of referral for treatment under sedation with a multiple logistic regression taking into account inter-relationships between the independent variables.Results-A direct signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
1
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 48 publications
5
73
1
7
Order By: Relevance
“…No entanto, em outras investigações, as meninas demonstraram maior ansiedade que os meninos em estudos nos quais se avaliou a ansiedade por meio de escalas e questionários 4,23,24 . Questionários de ansiedade são respondidos pelas meninas com maior constrangimento, predispondo-as, desta forma, a se mostrarem mais ansiosas.…”
Section: Discussionunclassified
“…No entanto, em outras investigações, as meninas demonstraram maior ansiedade que os meninos em estudos nos quais se avaliou a ansiedade por meio de escalas e questionários 4,23,24 . Questionários de ansiedade são respondidos pelas meninas com maior constrangimento, predispondo-as, desta forma, a se mostrarem mais ansiosas.…”
Section: Discussionunclassified
“…Similarly, having a past perceived bad experience was ascertained highly associated with the level of dental anxiety in another study. 26 Heaton et al 27 also reported on the fact that higher dental fear survey scores were related to past avoidance of dental care regarding a bad experience for the prediction of higher observed anxiety. The results of the present study were in agreement with previous studies indicating the negative dental experience in their lives had significantly associated higher scores of dental fear.…”
Section: Discussionmentioning
confidence: 99%
“…According to the distribution of total scores, the MDFS survey's results were stratified into 3 equal levels of dental fear such as low (14)(15)(16)(17)(18), medium (19)(20)(21)(22)(23)(24)(25)(26)(27), high . The distribution of dental fear in the participant group that regularly visit their dentists was 9.3% (n = 18) low level, 3.8% (n = 8) medium level and 4.9% (n = 10), while the 83.8% (n=176) of the participants who go to the dental health and care center just when they have a relevant complaint tend to show a medium level of dental fear (p = 0.015).…”
Section: Resultsmentioning
confidence: 99%
“…16 This high perceived need leads to feelings of negative social evaluation, and powerless 23 as well as having a negative effect on their attitude towards dental attendance. 24 This potentially has an impact on work situations, personal life and relationships with family members 1,6,25 which are affected by their negative thoughts and feelings, lack of selfesteem/confidence and sleep. 23 The data presented in this study is extracted from ADHS.…”
Section: Discussionmentioning
confidence: 99%